Comparison of Investment Activity of the Russian and Foreign Manufacturers: Case from Manufacturing of Transportation Vehicles - Spitsin, Vladislav; Mikhalchuk, Aleksandr; Zalmezh, Vladimir; Antonova, Irina; Tsekhanovsky, Igor; Zadorozhnyi, Valeriy; Shabaldina, Nataliya; Dorzheeva, Larisa (International Journal of Economics and Financial Issues, 2016)
The purpose of this paper is to study the indices of investment activity of subsection DM «Manufacturing of transportation vehicles and equipment» enterprises under Russian, foreign and joint ownership. Multivariate statistical analysis of the investment activity was performed at the Russian regional level. Using analysis of variance we identified statistically significant differences of the investment to shipped products ratio and investment structure in fixed capital between Russian, foreign and joint ownership enterprises. Using methods of hierarchical classification, two models of clustering of regions were performed for each form of ownership. The clustering demonstrated that during the years of 2010-2013 the process of intensive creation of enterprises under foreign ownership in certain regions of Russia continued. In regions with enterprises under Russian and joint ownership a low intensity of investment processes was identified. Some region clusters with enterprises under joint ownership have high share of investment into foreign machinery and equipment. Keywords: Domestic and foreign and joint enterprises, manufacturing of transportation vehicles, investments, multivariate statistical analysis. JEL Classifications: C100, G310, L620, O140